2018
DOI: 10.1136/bmj.k5166
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the new medical examiner role on patient safety

Abstract: Alan Fletcher and colleagues outline how the new medical examiner system could create a world leading mortality review system if implemented appropriately

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…Analysis of ME reviews in one of the pilot services identified clinical governance issues in 4% of cases that attending doctors were unaware of, including system failures highlighted by bereaved relatives. 6 This is consistent with ME accounts of the value of feedback from relatives and represents a strength of this approach.…”
Section: Findings In the Context Of Relevant Researchsupporting
confidence: 79%
See 1 more Smart Citation
“…Analysis of ME reviews in one of the pilot services identified clinical governance issues in 4% of cases that attending doctors were unaware of, including system failures highlighted by bereaved relatives. 6 This is consistent with ME accounts of the value of feedback from relatives and represents a strength of this approach.…”
Section: Findings In the Context Of Relevant Researchsupporting
confidence: 79%
“…5 The ME role was introduced to provide scrutiny by an independent, senior doctor of all deaths not investigated by a coroner. 6 The Coroners and Justice Act 2009 provides the legal basis for this new role, but it is not yet a statutory requirement. 7 The main aims of the ME role are to ensure that the Medical Certificate of Cause of Death (MCCD) is as accurate as possible, that…”
Section: Introductionmentioning
confidence: 99%
“…To utilise better, this would require a degree of central organisation at regional or national level. The introduction of the Medical Examiner system, in England and Wales [15] may present an opportunity to do this but hitherto the focus has been almost entirely on patient satisfaction (or, more strictly, that of their relatives) and healthcare quality. Whilst important, this ignores the usages that mortality statistics have been put to, historically, to tackle other areas of public health such as health protection and health promotion, such as Clean Air Acts, following the 1953 London smog or the current tracking of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…To utilise better, this would require a degree of central organisation at regional or national level. The introduction of the Medical Examiner system, in England and Wales 14 may present an opportunity to do this but hitherto the focus has been almost entirely on patient satisfaction (or, more strictly, that of their relatives) and healthcare quality. Whilst important, this ignores the usages that mortality statistics have been put to, historically, to tackle other areas of public health such as health protection and health promotion, such as Clean Air Acts, following the 1953 London smog or the current tracking of Covid-19.…”
Section: Discussionmentioning
confidence: 99%